2019
DOI: 10.1056/nejmoa1909953
|View full text |Cite
|
Sign up to set email alerts
|

Final Analysis of a Trial of M72/AS01E Vaccine to Prevent Tuberculosis

Abstract: BACKGROUNDResults of an earlier analysis of a trial of the M72/AS01 E candidate vaccine against Mycobacterium tuberculosis showed that in infected adults, the vaccine provided 54.0% protection against active pulmonary tuberculosis disease, without evident safety concerns. We now report the results of the 3-year final analysis of efficacy, safety, and immunogenicity. METHODSFrom August 2014 through November 2015, we enrolled adults 18 to 50 years of age with M. tuberculosis infection (defined by positive result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
340
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 418 publications
(374 citation statements)
references
References 9 publications
(17 reference statements)
6
340
0
5
Order By: Relevance
“…To boost or replace BCG, multiple TB vaccine candidates have been proposed and are being evaluated in different higher end preclinical or clinical phase 1 and phase 2 studies (7). Recently one subunit vaccine candidate, M72/AS01E, induced significant protection from developing TB in a LTBI population (8,9). Although the numbers of prevented cases were relatively low as yet (10 TB cases in the M72/AS01E group vs. 22 TB cases in the placebo group, a vaccine efficacy of 54%), the outcome of this phase IIb trial supports the power of rational Mtb antigen-based subunit TB vaccine development.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…To boost or replace BCG, multiple TB vaccine candidates have been proposed and are being evaluated in different higher end preclinical or clinical phase 1 and phase 2 studies (7). Recently one subunit vaccine candidate, M72/AS01E, induced significant protection from developing TB in a LTBI population (8,9). Although the numbers of prevented cases were relatively low as yet (10 TB cases in the M72/AS01E group vs. 22 TB cases in the placebo group, a vaccine efficacy of 54%), the outcome of this phase IIb trial supports the power of rational Mtb antigen-based subunit TB vaccine development.…”
mentioning
confidence: 63%
“…However, the immune response of adolescents is not often analyzed as a separate entity but merged with that found in either children (48,64) or adults (37). The need for carefully considering different age groups is supported by the M72/AS01E efficacy trial results, which showed that the highest vaccine efficacy in preventing active TB among LTBI was in individuals of 25 years of age or younger, after 2.5 years of follow up (8,9). This observed age-effect has been explained by possibly different timing of primary Mtb infection occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of individuals successfully control Mycobacterium tuberculosis (Mtb) infection in a clinically asymptomatic state termed latent TB infection (LTBI)(1). Individuals with LTBI are defined as having a positive tuberculin skin test (TST) and/or Interferon-gamma Release Assay (IGRA), a normal chest radiograph and the absence of clinical signs and symptoms of disease(2). Latently-infected individuals are generally thought to contain Mtb within granulomatous lesions in the lung without completely eradicating bacteria, although direct evidence for the persistence of Mtb in human LTBI is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a phase 2b trial of the M72/AS01 E vaccine in Africa showed vaccine efficacy of 50% at 3 years for MTB-infected, HIV-negative adults against active pulmonary TB, representing a major breakthrough. 19 TB control programmes and health services need to be strengthened to realize the potential of these recent scientific advances. Political leadership and accountability, sustainable funding and investment in research and development, and, not least, addressing the societal and poverty-related drivers of the TB epidemic will be vital in order to achieve WHO's ambitious goal to 'End TB by 2030'.…”
mentioning
confidence: 99%